2014
DOI: 10.1111/1471-0528.12978
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of pre‐eclampsia in migrant relative to native Norwegian women: a population‐based study

Abstract: Objective To compare the prevalence of pre-eclampsia in migrant women with Norwegian women, and to study the prevalence of pre-eclampsia by length of residence in Norway.Design Observational study.Setting The Medical Birth Registry of Norway.Population All Norwegian, Pakistani, Vietnamese, Somali, Sri Lankan, Filipino, Iraqi, Thai and Afghan women who gave birth after 20 weeks of gestation during the period 1986-2005 in Norway.Methods The prevalence of pre-eclampsia was calculated by country of birth. The asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
42
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 40 publications
7
42
1
4
Order By: Relevance
“…Our results are in line with similar findings in Swedish studies that women born outside of Nordic countries had at least a similar or lower risk of HDP than women born in Nordic countries . An earlier study from Norway assessing deliveries in a time period with a lower number of immigrants in Norway than in our study (1986‐2005) compared specific immigrant groups with Norwegian women and found similar or lower prevalence and risk of preeclampsia among immigrants, with the exception of Somalis . In our study, the prevalence of PE was highest among women born in sub‐Saharan Africa, but after adjustment with other covariates these women had a similar risk of PE compared with Norwegian‐born women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with similar findings in Swedish studies that women born outside of Nordic countries had at least a similar or lower risk of HDP than women born in Nordic countries . An earlier study from Norway assessing deliveries in a time period with a lower number of immigrants in Norway than in our study (1986‐2005) compared specific immigrant groups with Norwegian women and found similar or lower prevalence and risk of preeclampsia among immigrants, with the exception of Somalis . In our study, the prevalence of PE was highest among women born in sub‐Saharan Africa, but after adjustment with other covariates these women had a similar risk of PE compared with Norwegian‐born women.…”
Section: Discussionsupporting
confidence: 92%
“…The strength of this study is its large population‐based dataset of almost 1 million deliveries during the study period, with a previously published validation study showing high validity of the preeclampsia diagnosis in the MBRN . All foreign‐born women delivering in Norway were included in this study, not merely specific immigrant groups as in previous studies . We performed multivariate regression analyses, which describe the complex covariation of the assessed risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar rates have been reported in other Nordic countries: according to the Danish hospital discharge registry 2.72% of women who gave birth in Northern Sealand in years 1998–2000 had preeclampsia [22]. In the medical birth registry data of Norway, covering 1 million births in years 1986–2005, preeclampsia rate was 3.7% [23]. While no validation studies exist for preeclampsia diagnoses in the Finnish healthcare registers, studies of the Norwegian [24] and Danish [22] registries have been validated against medical records according to criteria similar to those used in the present study.…”
Section: Discussionsupporting
confidence: 68%
“…Another limitation is the lack of data on ethnicity. Immigrant women have more often preterm birth [20], but less often preeclampsia [21]. Thus, the association between preterm birth and later preeclampsia would likely not be caused by failure of adjusting for ethnicity.…”
Section: Discussionmentioning
confidence: 99%